2017
DOI: 10.1093/annonc/mdx078
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized, open-label, phase 2 study of everolimus in combination with pasireotide LAR or everolimus alone in advanced, well-differentiated, progressive pancreatic neuroendocrine tumors: COOPERATE-2 trial

Abstract: The addition of pasireotide to everolimus was not associated with the improvement in PFS compared with everolimus alone in this study. Further studies to delineate mechanisms by which SSAs slow tumor growth in NET are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 27 publications
3
92
0
2
Order By: Relevance
“…In one of these trials, everolimus was explored in combination with the novel SSA pasireotide, an upstream activator of the mTOR pathway without any benefit in the PFS [24] . Another trial investigated the combination of everolimus and the angiogenesis inhibitor bevacizumab that binds circulating VEGF compared to everolimus alone [25] .…”
Section: Discussionmentioning
confidence: 99%
“…In one of these trials, everolimus was explored in combination with the novel SSA pasireotide, an upstream activator of the mTOR pathway without any benefit in the PFS [24] . Another trial investigated the combination of everolimus and the angiogenesis inhibitor bevacizumab that binds circulating VEGF compared to everolimus alone [25] .…”
Section: Discussionmentioning
confidence: 99%
“…17 Everolimus combined with the long-acting somatostatin analog pasireotide LAR was evaluated in a phase II randomized controlled trial in 160 patients with advanced progressive PNETs in the multinational COOPERATE-2 study, which reported a median PFS of 16.8 months versus 16.6 months for everolimus alone. 18 The objective response showed PR advantage for the combination (20.3% vs. 6.2%), but stabilization of disease was comparable in the two groups. Grade 3/4 toxicity in respect of fasting hyperglycemia was increased in the combination group (37% vs. 11%).…”
mentioning
confidence: 89%
“…Grade 3/4 toxicity in respect of fasting hyperglycemia was increased in the combination group (37% vs. 11%). 18 Contemporary clinical investigation of molecular targeted therapeutics may overlook agents that work most effectively in combination with radiation. 12 Co-development of innovative drug combinations with radionuclide therapy, such as that explored in our phase IB study of 177 Lu-octreotate PRRT and everolimus, directed simultaneously at multiple therapeutic targets, has the potential to improve the response to treatment.…”
mentioning
confidence: 99%
“…In one of these trials, everolimus was explored in combination with a novel somatostatin analogue, pasireotide that binds to four of five somatostatin receptors and downregulates IGF-1, an upstream activator of the mTOR pathway (Kulke et al 2015c). Another trial investigated the combination of everolimus and an angiogenesis inhibitor, bevacizumab, which binds circulating VEGF (Kulke et al 2015b).…”
Section: Combination Therapiesmentioning
confidence: 99%